Failure analysis of EB-PVD LaZrCeO/YSZ TBCs exposed to molten NaCl in thermal cycling. Issue 21 (1st November 2022) - Liu, Yang; Xie, Min; Li, Ruiyi; Pei, Xun; Zhang, Yonghe; Mu, Rende; Bao, Jinxiao; Song, Xiwen
Abstract: This study focuses on understanding the corrosion behavior of LaZrCeO/YSZ (LZC/YSZ) coatings exposed to molten NaCl at high temperatures and compares it with that of YSZ coating. There is significant damage in LZC/YSZ coatings compared with YSZ coating, attributed to the synergistic effect of the thermal growth stress introduced by thermal growth oxide thickening, thermal stress caused by the thermal expansion mismatch between the double ceramic layers (DCLs), and the degradation of the bond coating. The lifetime of LZC/YSZ coatings was reduced significantly in the molten NaCl. The thermal mismatch stress between the DCLs was considered to be the main reason why the damage to the LZC/YSZ coatings was more serious than that to the YSZ coating.